Insect and Mite Pest Management in Florida Peanut - Isaac L. Esquivel; Xavier Martini; Ethan Carter; Silvana V. Paula-Moraes (EDIS)
Peanut is one of the most important cash crops grown in the United States, with an estimated production value of over $1 billion. The southeastern coastal plains harbor most of the US peanut acreage, and Florida is ranked among the top five major peanut producers in the US, with 160 thousand acres planted in 2022 and an annual production value of $130 million in 2021. The majority of peanut acreage in Florida is in the Panhandle and central Florida, in Jackson, Santa Rosa, and Levy counties. Several insect pests feed on various peanut plant parts, including foliage, roots, and fruiting structures. These pests can cause significant damage to the plant canopy and kernels and can also transmit diseases, reducing the quality and quantity of yield if they are not properly detected and managed. This publication serves as a guide for Extension agents and growers to provide an overview of proper sampling techniques and management for peanut pests found in the Florida Panhandle.